A comparison of kinematics between elite handball players with and without shoulder pain after a functional fatigue protocol - Torabi, T. P.; Bencke, J.; Van den Tillaar, R. (ISBS Proceedings Archive (Michigan), 2022)
Shoulder pain are common in team handball, and players often continue playing despite pain. The aim of the study was to investigate whether a functional fatigue protocol (FFP) affects throwing kinematics, and whether this effect was different between players with and without shoulder pain. Thirty female players performed maximal standing throws before and after a FFP, while joint kinematics were measured with eight cameras (Vicon T40, Oxford, UK). The main findings were that fatigue affected throwing velocity positively. Some kinematic parameters in both groups were affected, but the effect on kinematics was not the same in both groups, especially timing of the maximal shoulder extension and minimal internal shoulder rotations seems to change differently between the groups after a FFP. No previous studies have investigated, whether functional fatigue influences throwing kinematic differently at team handball players who are playing with or without shoulder pain.